Злі/добрі чужинці: євреї та цигани в російських народних легендах - Руйє-Віллоубі, Ж. (Народна творчість та етнологія, 2012)
Jeanmarie Rouhier-Willoughby. The (Un)Clean Other: Jews and Roma in Russian Folk Legends. The perception of the other in legends is not nearly as straightforward an issue as it would seem. Certainly, one could point to the depictions of Jews and Roma and safely assert that legends were responsible for misinformation and stereotypes about these people. We can safely conclude that the legend itself does not create stereotypes, but builds on those that already exist. I would contend that the Roma and Jews provide cover for the narrators to criticize God and Нis Сhurch.